Скандинавська модель трансферу технологій: досвід та особливості - Дума, О. І.; Duma, O. I. (Видавництво Львівської політехніки, 2021)
Наведено результати дослідження особливостей Скандинавської моделі трансферу технологій, яка продемонструвала свою ефективність у Норвегії, Швеції та Фінляндії. Описано результати функціонування трансферу технологій в інноваційній екосистемі цих країн, через їх місце у міжнародних рейтингах інновацій. Для оцінювання результативності функціонування трансферу технологій запропоновано застосовувати шести критерійну шкалу, яка містить: індекс розвитку людського потенціалу, глобальний індекс знань, рейтинг легкості ведення бізнесу, глобальний індекс інновацій, глобальний індекс конкурентоспроможності та індекс захисту прав власності. Проаналізовано особливості функціонування механізмів трансферу технологій у Норвегії, Швеції та Фінляндії. Визначено особливості цих субмоделей, які визначають їхню ефективність, а, з іншого боку, можуть і мають бути залучені в українську практику трансферу технологій

The article presents the results of a scientific research the features of the Scandinavian model of technology transfer, which has demonstrated its effectiveness in Norway, Sweden and Finland. The Scandinavian model of technology transfer has been formed for a long time and has been subject to significant experiments by the governments of these countries, research centers, universities and business structures, which sought an effective model of organizing the innovation process from the perspective of their own goals and interests. The article presents the results of the functioning of technology transfer in the innovation ecosystem of these countries, through their place in the international rankings of innovations and related rankings. It is proposed to use a six-criteria scale to assess the effectiveness of technology transfer, which contains: Human development index, Global knowlede Index, Doing business, Global Innovations Index, The Global Competitiveness Index, The International Property Right Index. The results of the innovation ecosystem of countries have their expression in micro- and macroeconomic indicators. Most of these indicators are taken into account when ranking countries in one or more indices proposed for six criteria scale. Assessing the condition of technology transfer through these six criteria scale makes it possible to determine the productivity and level of organization of technology transfer in the country. The article analyzes the peculiarities of the functioning of technology transfer mechanisms in Norway, Sweden and Finland. The analysis revealed that the three countries studied have their own preconditions and priorities for the development of the innovation ecosystem. Nevertheless, there are a number of features that are common and fundamental for effective technology transfer in each. One of the important elements of effective technology transfer in the Scandinavian countries are universities and technology transfer centers in universities. Therefore, the article also explores the functions and tasks of technology transfer centers in Scandinavian universities. The peculiarities of the Scandinavian model, which determine its efficiency, have been researched, on the other hand, this peculiarities can and should be implemented in the Ukrainian practice of technology transfer.
Scandinavian technology transfer model: experience and insights
Keywords: трансфер технологій; модель трансферу технологій; Скандинавська модель трансферу технологій; інноваційні кластери; Business Finland; шести критерійна шкала оцінки трансферу технологій; technology transfer; technology transfer model; Scandinavian technology transfer model; innovation clusters; Business Finland; six-criteria scale of technology transfer assessment; 339.92; 330.341.1